2019
DOI: 10.2174/1570159x17666190409144558
|View full text |Cite
|
Sign up to set email alerts
|

Monoamines and their Derivatives on GPCRs: Potential Therapy for Alzheimer’s Disease

Abstract: Albeit cholinergic depletion remains the key event in Alzheimer’s Disease (AD), recent information describes stronger links between monoamines (trace amines, catecholamines, histamine, serotonin, and melatonin) and AD than those known in the past century. Therefore, new drug design strategies focus efforts to translate the scope on these topics and to offer new drugs which can be applied as therapeutic tools in AD. In the present work, we reviewed the state-of-art regarding genetic, neuropathology and neuroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 239 publications
0
9
0
Order By: Relevance
“…Next, the matching rate of one of the two factors with druggable GPCRs (Figure 3a) was reminiscent of the result obtained from Alzheimer's disease (AD) and monogenic hypertension (MH), which resulted in the matches of either of the two factors and the disease at ~84% (59 of 70 genes susceptible to AD; 66 of 79 genes causative of MH) [69,70]. Indeed, GPCRs become important targets in understanding the molecular mechanisms underlying AD [144][145][146][147][148] and hypertension [134][135][136][137][138][139][140][141][142][143]. Inconsistent with the prior reports [69,70], however, there was an atypical significant relationship in proximity to telomeres with respect to the molecular size (FL) of the druggable GPCRs (Figure 3b,c).…”
Section: Discussionmentioning
confidence: 91%
“…Next, the matching rate of one of the two factors with druggable GPCRs (Figure 3a) was reminiscent of the result obtained from Alzheimer's disease (AD) and monogenic hypertension (MH), which resulted in the matches of either of the two factors and the disease at ~84% (59 of 70 genes susceptible to AD; 66 of 79 genes causative of MH) [69,70]. Indeed, GPCRs become important targets in understanding the molecular mechanisms underlying AD [144][145][146][147][148] and hypertension [134][135][136][137][138][139][140][141][142][143]. Inconsistent with the prior reports [69,70], however, there was an atypical significant relationship in proximity to telomeres with respect to the molecular size (FL) of the druggable GPCRs (Figure 3b,c).…”
Section: Discussionmentioning
confidence: 91%
“…These shorter latencies are related to the decreased levels of androgens in rats [ 35 ] and are in line with memory disruption related to androgens decreasing in humans [ 36 , 37 ]. In rats, steroid decreasing causes effects in the synthesis and degradation of key neurotransmitters such as acetylcholine, catecholamines, and other monoamines [ 8 , 38 , 39 ], including melatonin [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, melatonin induces beneficial effects on the cholinergic system by increasing acetylcholine release and inhibiting choline acetyltransferase [ 7 ]. Furthermore, it also appears to exert benefits linked to the modulation of other monoamine systems, such as the serotonergic and dopaminergic systems by means of unestablished mechanisms [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies of post-mortem AD brains have shown changes in monoamine transmitter systems including serotonin [6], noradrenalin [7], histamine [8], and ACh [35] which tend to show early and severe damage. Low monoamine levels have been found, which precede the loss of its producing neurons [36]. For this reason, significant efforts have been made to determine the relationship between neurotransmitters dysfunction and AD pathogenesis [37].…”
Section: Dysregulation Of the Neurotransmission Systems Involved In Admentioning
confidence: 99%